2004
DOI: 10.1081/dmr-120033997
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Mechanism of Tamoxifen in Developing Endometrial Cancer

Abstract: Increased risk of developing endometrial cancers has been observed in women treated with tamoxifen (TAM), a widely used drug for breast cancer therapy and chemoprevention. The carcinogenic effect may be due to genotoxic DNA damage induced by TAM. In fact, TAM-DNA adducts were detected in the endometrium of women treated with this drug. TAM is alpha-hydroxylated by cytochrome P450 3A4 followed by O-sulfonation by hydroxysteroid sulfotransferase, and reacts with guanine residues in DNA, resulting in the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 76 publications
2
51
1
Order By: Relevance
“…at ASPET Journals on May 12, 2018 dmd.aspetjournals.org sponsible for the tamoxifen-induced lesions in the human endometrium, but the underlying mechanisms are not fully understood (Kim et al, 2004;Shang, 2006). The present study showed that short-term incubation with tamoxifen caused tamoxifen adduct formation and increased expression of the stress proteins GRP78 and activated caspase 3 in the glandular and surface epithelia of human endometrial explants, whereas there was no expression of stress proteins in the stroma.…”
Section: Tamoxifen Adducts and Cell Stress In Endometrial Glandsmentioning
confidence: 59%
See 1 more Smart Citation
“…at ASPET Journals on May 12, 2018 dmd.aspetjournals.org sponsible for the tamoxifen-induced lesions in the human endometrium, but the underlying mechanisms are not fully understood (Kim et al, 2004;Shang, 2006). The present study showed that short-term incubation with tamoxifen caused tamoxifen adduct formation and increased expression of the stress proteins GRP78 and activated caspase 3 in the glandular and surface epithelia of human endometrial explants, whereas there was no expression of stress proteins in the stroma.…”
Section: Tamoxifen Adducts and Cell Stress In Endometrial Glandsmentioning
confidence: 59%
“…In addition, tamoxifen protein adducts have been detected in human liver microsomes (Dehal and Kupfer, 1996). Both DNA adduct formation and estrogenic effects have been suggested as the mechanism by which tamoxifen induces cancer in the human endometrium (Kim et al, 2004;Shang, 2006). Attempts to determine whether tamoxifen therapy can lead to DNA adducts in the human endometrium have yielded conflicting results (Greaves et al, 1993;Hemminki et al, 1996;Carmichael et al, 1999;Shibutani et al, 2000;Sharma et al, 2003b;Beland et al, 2004).…”
mentioning
confidence: 99%
“…TAM may work as a mild tumor promoter by way of its weak estrogenic activity on the endometrium (4). Alternatively, TAM may play an additional role as a tumor initiator via its weak genotoxicant metabolites (5).…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome P450 converts TAM to ␣-hydroxytamoxifen (␣-OHTAM), N-desmethyltamoxifen (N-desTAM), and 4-hydroxytamoxifen (4-OHTAM) ( Fig. 1) (reviewed by Kim et al, 2004). Tamoxifen N-oxide (TAM N-oxide) is produced from TAM by flavincontaining monooxygenase.…”
mentioning
confidence: 99%
“…The cellular mechanism underlying TAM-induced carcinogenesis may be due to its partial estrogenic effect through the estrogen receptors and/or genotoxic damage (reviewed by Kim et al, 2004). Actually, a high level of TAM-DNA adducts produced in the liver of rats (Han and Liehr, 1992;Osborne et al, 1996) initiates the development of hepatocellular carcinomas (Hard et al, 1993).…”
mentioning
confidence: 99%